The Dual Role of Revenue Concentration in Corporate Landbanking: Evidence from Urbanizing Property Markets - Ardo Ryan Dwitanto; Adler Haymans Manurung; Nera Marinda Machdar; Wastam Wahyu Hidayat (CV. Creative Tugu Pena, 2026)
This study examines the determinants of corporate landbanking behavior by integrating macroeconomic demand factors with firm-level strategic characteristics. Focusing on publicly listed property developers in Indonesia, it investigates how urbanization and exchange rate uncertainty influence landbanking decisions, and how these effects are conditioned by firms’ revenue concentration. Using panel data regression analysis, the results show that urbanization significantly increases landbanking, confirming its role as a key demand-side driver in property markets. Exchange rate uncertainty also has a positive effect, suggesting that firms use landbanking as a strategic tool to preserve flexibility under macroeconomic volatility. At the firm level, revenue concentration is positively associated with landbanking, indicating that more focused firms allocate greater resources to land as a core strategic asset. More importantly, this study introduces a dual-effect perspective in which revenue concentration simultaneously increases baseline landholding while reducing firms’ responsiveness to external demand shocks. The negative interaction effect implies that, although concentrated firms hold larger landbanks, they adjust their land accumulation less aggressively in response to urbanization than more diversified firms. By integrating insights from urban economics, real estate, and corporate strategy, this study contributes to the literature by highlighting the role of firm heterogeneity in shaping land supply behavior. The findings also offer policy implications, suggesting that land-use regulations should account for differences in firm structure to improve housing supply responsiveness in rapidly urbanizing economies.